Design, automated synthesis and immunological evaluation of NOD2-ligand–antigen conjugates - Willems, Marian M. J. H. P.; Zom, Gijs G.; Meeuwenoord, Nico; Ossendorp, Ferry A.; Overkleeft, Herman S.; van der Marel, Gijsbert A.; Codée, Jeroen D. C.; Filippov, Dmitri V. (Beilstein Journal of Organic Chemistry, 2014)
The covalent attachment of an innate immune system stimulating agent to an antigen can provide active vaccine modalities capable of eliciting a potent immune response against the incorporated antigen. Here we describe the design, automated synthesis and immunological evaluation of a set of four muramyl dipeptide–peptide antigen conjugates. Muramyl dipeptide (MDP) represents a well-known ligand for the intracellular NOD2 receptor and our study shows that covalently linking an MDP-moiety to an antigenic peptide can lead to a construct that is capable of stimulating the NOD2 receptor if the ligand is attached at the anomeric center of the muramic acid. The constructs can be processed by dendritic cells (DCs) and the conjugation does not adversely affect the presentation of the incorporated SIINFEKL epitope on MHC-I molecules. However, stimulation of the NOD2 receptor in DCs was not sufficient to provide a strong immunostimulatory signal.
Keywords: automated synthesis; glycopeptide; innate immunity; muramyl dipeptide; NOD2 receptor; solid phase synthesis